The Missing Links: Towards the Effective Management and Control of Corruption in Nigeria, Africa and the Global South - Lawrence, Ethelbert Okey (International Journal of Criminology and Sociology, 2016)
Corruption has become a full blown cancer in Nigeria, Africa and other Global South countries, consequently bringing about economic backwardness, political instability, social insecurity, infrastructural decay, unaccountability, negation of the principle of law, etc. Efforts towards curbing it have failed woefully. It is evident that there are missing links towards effective management and control of the phenomenon in these areas. Based on secondary data, and using Nigeria as sample, this paper examined these missing links towards effective management and control of the phenomenon. Since corruption is multi-faceted i.e. manifests through multiplicity of factors ranging from ethno-religious, and sectional sentiments on one hand, and on the other, reflected in the social classes of active, and non-active players of the phenomenon; as well as international factors sustaining the menace; not leaving the mechanisms for control and management of the whole process of its prevalence. Thus, an integrative theoretical approach was used to explain these missing links which have been identified as corrupt individuals in the corridors of power; defective/imbalance of political and social structure; legal justice; social justice; and international collaboration. Findings reveal: political powers in the hands of corrupt individuals; poor implementation of legal and social justice among others account for the persistence of corruption in these areas. Some of the recommendations include: having individuals with proven records of integrity vie for political elective positions; there should be no sacred cows in the fight against corruption; and, there should be a redefinition of the core values to define corruption.